Association between platelet glycoprotein Ia C807T gene polymorphism and ischemic stroke: a meta-analysis in a separate ethnic group - Huang, Xiao-Yun; Fu, Wen-Jin; Mei, Zhi-Zhong; Yu, Ying-Li; Huang, Yi-Hong; Lin, Han; Chen, Jian-Jun; Wang, Ming-Xia; Guan, Shao-Bing; Fang, Hao-Wei (Cellular and Molecular Biology, 2017)
Many studies have been examined the association of platelet glycoprotein (GP) Ia C807T polymorphism with ischemic stroke (IS) susceptibility. However, the results of these studies are inconsistent. To further assess the effects of GP Ia C807T polymorphism on the risk of IS, a meta-analysis was performed in a separate ethnic group. Relevant studies were identified using PubMed and Chinese databases through January 2017. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) were used to assess the strength of the associations. Finally, 13 studies contained 2438 IS cases and 2308 controls included. In the total analyses, a significantly elevated risk of IS was associated with all variants of GP Ia C807T in the Chinese population (T vs C: OR = 1.24, 95% CI = 1.09-1.40; TT vs CC: OR = 1.59, 95% CI = 1.17-2.15; TT and CT combined vs CC: OR = 1.32, 95% CI = 1.09-1.59; TT vs CC and CT: OR = 1.35, 95% CI = 1.04-1.76). In the subgroup analyses stratified by ethnicity and geographic areas, it revealed the significant results in Chinese Han and in South China. This meta-analysis provides the evidence that GP Ia C807T polymorphism may contribute to the IS development in the Chinese population, especially in South China, and further studies in other ethic groups are required for definite conclusions.